PENGARUH KOMPENSASI, KEAHLIAN, MOTIVASI, DAN DISIPLIN KERJA TERHADAP PRESTASI KERJA KARYAWAN LSM SINTESA UNIT BANTESA CABANG KONAWE - Tauwi Tauwi (Jurnal Akrab Juara, 2019)
This study shows that the effect of compensation, expertise, motivation, and work discipline on the work performance of NGO employees synthesizing the konawe branch of Bantesa unit is highly expected so that more workers have high performance, the overall productivity of the organization will increase so that it can survive in global competition. employees are required to be able to complete their duties and responsibilities effectively and efficiently. Employee success can be measured through customer satisfaction, reduced number of complaints and optimal target achievement. The performance of employees at LPSM Synthesis can also be measured through the completion of their tasks effectively and efficiently and perform their roles and functions and all of them are linearly related and positively related to the success of a company. Based on the results of the Influence research given the four independent variables are positive, meaning that the better compensation, expertise, motivation, and work discipline will result in the better work performance of the employees produced. The Compensation variable has a positive and significant effect on work performance at the Bantesa Branch Konawe Synthesis Lsm office. This means that the better the compensation, the better the work performance of employees.